Analisis Beberapa Faktor Yang Mempengaruhi KinerjaKaryawan (Studi Pada Ayam-Ayam Resto Klodran) - Yudha, Diky Arditya, Drs. Kusdiyanto, SE, MSi (2017)
This study aims to determine the effect of work motivation, ability to work, and the work environment to employees performance at Ayam-Ayam Resto Klodran. The population in this study as many as 70 employees and samples taken as many as 42 employees. Mechanical analysis of the study include validity, reliability, classic assumption test, and regression analysis. The findings are partially and simultaneously work motivation, ability to work, and working environment have a significant effect on employee performance. Of work motivation, ability to work, and the work environment is able to explain the performance of employees is 56.5% and the rest are still there other variables that influence amounted to 43.5%